Corporate social responsibility and the reproduction of (neo)colonialism in the Ecuadorian Amazon. Issue 3 (July 2019) - Pearson, Zoe; Ellingrod, Sara; Billo, Emily; McSweeney, Kendra
Highlights: Colonial epistemologies communicated through Repsol's CSR programs reinforce neocolonial social relations. Research attuned to micro-scale relationships, discourses, and everyday life can reveal insights into how institutions like CSR operate. We provide a postcolonial critique of CSR that has implications within and beyond Ecuador. Abstract: Ecuador's famed Yasuní National Park is home to Waorani indigenous communities and the Block 16 oil concession, operated by Repsol oil and gas company. Inspired by feminist geographic methodology we carried out qualitative research on Repsol's Corporate Social Responsibility (CSR) programs in the Waorani communities of northern Block 16/Yasuní, with attention to the micro-scale relationships, discourses, and everyday social relations enacted through CSR. In doing so we demonstrate how a better understanding of these dynamics can help to shed light on the ways that CSR produces forms of intimate governance that ultimately serve to facilitate resource extraction. Specifically, we argue that colonial epistemologies communicated through Repsol's CSR programs reinforce neocolonial social relations between Waorani residents and the people facilitating Repsol's CSR programming. This serves to assert Repsol's legitimacy and belonging as a territorial authority in this place, facilitating the company's ongoing oil extraction and the state's larger project of neo-extractivism. Our grounded analysis contributes a unique perspective on how CSR efforts function between a multinational oil company and indigenous communities, providing a postcolonial critique that has implications within and beyond Ecuador for how hierarchical colonial relationships are reproduced over historically subjugated populations through CSR.